Sosialisasi tentang pendekatan kontekstual dalam pembelajaran kepada guru dan peserta didik di Sekolah Dasar Inpres 30 Aitinyo, Kabupaten Maybrat: Socialization for teachers and students on contextual learning approaches at Primary School of Inpres 30 Aitinyo, Maybrat Regency - Nunaki, Jan H.; Santoso, Budi; Rumatumia, Zainudin; Inggesi, Barsalina J (IGKOJEI: Jurnal Pengabdian Masyarakat, 2025)
ABSTRACT  The contextual learning approach is a strategy that emphasizes the connection between subject matter and students' real-life experiences. However, understanding and application of this approach are still limited in several elementary schools in rural areas, including SD Inpres 30 Aitinyo, Maybrat Regency. This community service activity aimed to provide teachers and students with information on the concept and implementation of a contextual approach in learning. The methods used included material delivery, interactive discussions, and learning simulations, involving 6 teachers and 57 students. The results of the activity showed that before the socialization, most teachers were still using a conventional approach that focused on memorization, with limitations in linking material to the local context. After the activity, there was an increase in teachers' understanding of designing context-based learning and increased student active involvement in the learning process. Teachers also began developing lesson plans that incorporated elements of the surrounding environment and local culture as learning resources. Students showed a positive response through their activeness and ability to relate material to everyday experiences. It was concluded that this activity successfully improved teachers' understanding and skills in applying a contextual approach and encouraged active student participation in more meaningful learning. It is hoped that this activity will be the first step towards implementing contextual learning on a sustainable basis in elementary schools in the Maybrat Regency area.  Keywords: Aitinyo; Approach, Teacher; Contextual; Student.   ABSTRAK  Pendekatan pembelajaran kontekstual merupakan strategi yang menekankan keterkaitan antara materi pelajaran dengan pengalaman nyata siswa dalam kehidupan sehari-hari. Namun, pemahaman dan penerapan pendekatan ini masih terbatas di beberapa sekolah dasar di wilayah pedesaan, termasuk SD Inpres 30 Aitinyo, Kabupaten Maybrat. Kegiatan pengabdian ini bertujuan untuk memberikan sosialisasi kepada guru dan peserta didik mengenai konsep dan implementasi pendekatan kontekstual dalam pembelajaran. Metode yang digunakan meliputi penyampaian materi, diskusi interaktif, dan simulasi pembelajaran dengan melibatkan 6 guru dan 57 siswa. Hasil kegiatan menunjukkan bahwa sebelum sosialisasi sebagian besar guru masih menerapkan pendekatan konvensional yang berfokus pada hafalan, dengan keterbatasan dalam mengaitkan materi dengan konteks lokal. Setelah kegiatan berlangsung, terjadi peningkatan pemahaman guru dalam merancang pembelajaran berbasis konteks serta meningkatnya keterlibatan aktif siswa dalam proses belajar. Para guru juga mulai menyusun rencana pembelajaran yang memasukkan unsur lingkungan sekitar dan budaya lokal sebagai sumber belajar. Siswa menunjukkan respons positif melalui keaktifan dan kemampuan mengaitkan materi dengan pengalaman sehari-hari. Disimpulkan bahwa kegiatan ini berhasil meningkatkan pemahaman dan keterampilan guru dalam menerapkan pendekatan kontekstual serta mendorong partisipasi aktif siswa dalam pembelajaran yang lebih bermakna. Diharapkan kegiatan ini menjadi langkah awal menuju implementasi pembelajaran kontekstual secara berkelanjutan di sekolah-sekolah dasar di wilayah Kabupaten Maybrat.    Kata kunci: Aitinyo; Guru; Kontekstual; Pendekatan; Siswa.